(untitled) - Gnap, Jozef; Jagelcak, Juraj; Gec, Drahomir (Doprava a spoje, 2009)
The issue to choose correct packaging belongs among important point in supply chain. The aim of the packaging is to protect the goods from transport and environmental stresses. Logistic service providers (LSP's) know the importance of suitable packaging for supply chain procedures as handling, loading and unloading, load securing, warehousing and carriage. Stabile packaging unit is suitable handling unit for supply chain.